A green, accurate and sensitive analytical method based on vortex assisted deep eutectic solvent-liquid phase microextraction for the determination of cobalt by slotted quartz tube flame atomic absorption spectrometry. (25th April 2020) - Tekin, Zeynep; Unutkan, Tuğçe; Erulaş, Fatih; Bakırdere, Emine Gülhan; Bakırdere, Sezgin
Highlights: A sensitive and accurate method was developed using a novel green solvent as DES. SQT was used in order to enhance the sensitivity of the system. The method has provided 67-fold enhancement when compared to FAAS. Recovery studies carried out with linden samples were satisfactory. Abstract: Preconcentration of cobalt was carried out with deep eutectic solvent based liquid phase microextraction (DES-LPME) for trace determination by a slotted quartz tube (SQT) attached flame atomic absorption spectrometry (FAAS) system. Choline chloride and phenol in a 1:2 M ratio was used as a green solvent to extract cobalt from the aqueous sample solution. Key parameters influencing the extraction efficiency of cobalt were examined and optimized. Under the conditions optimized, the linear dynamic range was found between 5.0 and 50 µg L −1, and the limits of detection and quantification (LOD and LOQ) were calculated as 2.0 and 6.6 µg L −1, respectively. The detection power of the conventional FAAS was improved upon by 67 folds using the optimized DES-LPME-SQT-FAAS method. The developed analytical method was successfully applied for the determination of cobalt in linden tea samples and the recovery results obtained for different spiked concentrations (20, 30 and 40 µg L −1 ) were remarkable (≈100%).